The Konsep Urban Farming Untuk Ketahanan Pangan Keluarga Masyarakat Desa Kampung Baru - Novita Indrawati; Ciptati Nugraha Pratiwi; Hanif Maruf Supardi; M. Fahrul Wafi; Fahrul Habib Azli Panjaitan; Ira Anggraini Anggraini; Sammi Adam Ramadhani Ramadhani; Rhalia Sabilillah; Desmurlita Ramadhani; Miftahul Jannah; Aura Tiffany Dika (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Urban farming is a supporter of aspects of the beauty of the city and the feasibility of using sustainable spatial planning. Urban Farming is also carried out to increase income or activities to produce foodstuffs for family consumption. The methods used in this work program are: 1) Socialization or education approach, 2) Participatory Rural Aprasial which involves the community in all activities, 3) Participatory Technology Development which utilizes appropriate technology to integrate with science and local wisdom, namely plant cultivation with the concept of urban farming. The Measuring Instrument used in this report is a descriptive measuring tool, namely observation. The observations made to be a measuring tool in this report are to see the level of response from the community. Another observation is to look at the level of participation from the community. Finally, the observation we made was by looking at the level of interest from the community. This activity is in seeing the success of the activities carried out, namely by looking at changes in the attitudes of the people of Kampung Baru Village. The expected result and achievement is an increase in the knowledge and skills of the people of Kampung Baru Village in maintaining their family's food security, through practical vegetable crop farming using the concept of urban farming.